A Proposal for a Structural Model of the Feline Calicivirus Protease Bound to the Substrate Peptide under Physiological Conditions - Masaru Yokoyama; Tomoichiro Oka; Hirotaka Takagi; Hirotatsu Kojima; Takayoshi Okabe; Tetsuo Nagano; Yukinobu Tohya; Hironori Sato (Frontiers in Microbiology, 2017)
Feline calicivirus (FCV) protease functions to cleave viral precursor proteins during productive infection. Previous studies have mapped a protease-coding region and six cleavage sites in viral precursor proteins. However, how the FCV protease interacts with its substrates remains unknown. To gain insights into the interactions, we constructed a molecular model of the FCV protease bound with the octapeptide containing a cleavage site of the capsid precursor protein by homology modeling and docking simulation. The complex model was used to screen for the substrate mimic from a chemical library by pharmacophore-based in silico screening. With this structure-based approach, we identified a compound that has physicochemical features and arrangement of the P3 and P4 sites of the substrate in the protease, is predicted to bind to FCV proteases in a mode similar to that of the authentic substrate, and has the ability to inhibit viral protease activity in vitro and in the cells, and to suppress viral replication in FCV-infected cells. The complex model was further subjected to molecular dynamics simulation to refine the enzyme-substrate interactions in solution. The simulation along with a variation study predicted that the authentic substrate and anti-FCV compound share a highly conserved binding site. These results suggest the validity of our in silico model for elucidating protease-substrate interactions during FCV replication and for developing antivirals.